Drought impact on the germination of selected energy grass species - Marek KOPECKÝ (Journal of Central European Agriculture, 2015)
In order to gain a sufficient amount of phytomass for the needs of eco-energetics, there are monocultural grasslands established on the arable land. In the context of the changing climate and more frequent periods of drought, it is important to look for grass species and varieties that are able to withstand these stress conditions. Influence of droughtness on germination of four selected energy grass species is decribed in paper. The investigated species were tall meadow oat (Arrhenatherum elatius L.) - the Median variety, orchard grass (Dactylis glomerata L.) - the Padania variety, tall wheatgrass (Elymus elongatus) - the Szarvasi-1 variety and reed canary grass (Phalaris arundinacea L.) - the Chrastava variety. Although the species differed in the germinability (p < 0.001), the significant differences in their drought resistence were not found (p > 0.05)